The Role of Employee Training and Organizational Culture Improving SME Performance with Innovation as a Mediator - Andar Budi Setiawan; Armanu Armanu (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The strategic role of SMEs in the Indonesian economy and the phenomena of declining performance as a result of the Covid-19 pandemic motivated author to research this sector. Various internal problems make it difficult for SMEs to improve their performance and competitiveness in a competitive business environment. Using the dynamic capability perspective, this study examines the influence of human resource configuration through employee training and organizational culture which is able to encourage innovation that improves SME performance. This study uses purposive sampling technique and data collection is done through questionnaires and interviews with 122 SMEs in East Java. Data analysis is carried out using PLS SEM. The research results show that employee training does not have a direct effect on SME performance, however employee training is able to encourage innovation which has an impact on improving SME performance On the other hand, organizational culture has a significant direct and indirect effect on SME performance trough innovation. Results of this study can be used as a consideration by SME owners in making business decisions in order to improve their performance. From the theoretical side, the results of this study confirm the dynamic capability theory by Teece and Pisano regarding the key role of innovation and Becker's opinion from a human resource management perspective which states that employee training must be designed systematically according to the long-term needs of the organization in order to have an impact on improving organizational performance.